In vitro drug permeation from chitosan pellets - Ferrari, Priscileila C. [UNESP]; Souza, Fagner M.; Giorgetti, Leandro; Oliveira, Giselle F. [UNESP]; Chaud, Marco V.; Ferraz, Humberto G.; Evangelista, Raul Cesar [UNESP] (Elsevier B.V., 2012)
The purpose of this study was to prepare and characterize coated pellets for controlled drug delivery. The influence of chitosan (CS) in pellets was evaluated by swelling, in vitro drug release and intestinal permeation assays. Pellets were coated with an enteric polymer, Kollicoat (R) MAE 30 DP, in a fluidized-bed apparatus and the coating formulations were based on a factorial design. Metronidazole (MT) released from coated and uncoated pellets were assessed by dissolution method using Apparatus I. Intestinal permeation was evaluated by everted intestinal sac model in rats, used to study the absorption of MT from coated pellets containing CS or not through the intestinal tissue. Although the film coating avoided drug dissolution in gastric medium, the overall drug release and intestinal permeation were dependent on the presence of CS. Thus, pellets containing CS show potential as a system for controlled drug delivery. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Pellets; Chitosan; Enteric coating; Metronidazole; Controlled drug delivery; Everted intestinal sac model